1971
DOI: 10.1042/bj1250829
|View full text |Cite
|
Sign up to set email alerts
|

The action of mono- and di-functional sulphur mustards on the ribonucleic acid-containing bacteriophage μ2

Abstract: Bacteriophage mu2 is inactivated by both mono- and di-functional sulphur mustards at relatively low extents of alkylation. No degradation of alkylated RNA was detected. Cross-linking of RNA to protein was observed with the difunctional agent, but this reaction was only a minor contribution to the inactivation. Analyses of the reaction products in bacteriophage RNA showed that, at the mean lethal doses, more than one mono-alkylation of guanine had occurred but the sum total of other types of RNA alkylation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1972
1972
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 37 publications
(33 reference statements)
2
12
0
Order By: Relevance
“…However, there was only a limited correlation between the length of the truncated polypeptide and the length of the RNA message up to the potential alkylation site. Shooter and co-workers (31) were also unable to detect any correlation between the relative number of alkylguanine derivatives (in a RNA-containing bacteriophage p2) and plaque forming ability, and have suggested that other minor alkylation products may be responsible for inactivation of the phage. Furthermore, the response of the ribosome to alkylation sites on RNA is currently not known.…”
Section: Translationmentioning
confidence: 98%
“…However, there was only a limited correlation between the length of the truncated polypeptide and the length of the RNA message up to the potential alkylation site. Shooter and co-workers (31) were also unable to detect any correlation between the relative number of alkylguanine derivatives (in a RNA-containing bacteriophage p2) and plaque forming ability, and have suggested that other minor alkylation products may be responsible for inactivation of the phage. Furthermore, the response of the ribosome to alkylation sites on RNA is currently not known.…”
Section: Translationmentioning
confidence: 98%
“…The unsaturated keto groups of DNA appear to be functional groups that are attacked by mustard alkylating agents. [10][11][12] Alternatively, compounds such as sodium thiosulfate may reduce the toxicity of mustard by direct chemical reaction with nucleic acid macromolecules. The observation that thiosulfate can be titrated against the active form of mustard gas 13 further suggests that this may be a possible mechanism of action for this type of antidote.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the exact in vivo consequence of aberrant RNA methylation is unclear. However, pioneering in vivo and in vitro alkylation studies employing RNA phages and polyribonucleic acid, respectively, provided the first insights into RNA damage biology [28][29][30][31]. In an elegant study, Shooter and colleagues related the toxicity of various alkylating agents towards an RNA phage to the formation of 1-meA, 3-meC and probably O 6 -meG, while the quantitatively dominating lesion 7-meG was more harmless [30].…”
Section: Dysfunctionmentioning
confidence: 99%